Nível de relação entre a assimetria esportiva e a assimetria de temperatura da pele dos membros inferiores de atletas profissionais de futebol Belo Horizonte - Jorge Lúcio Rodrigues Júnior (2018)
Soccer involves performing a lot of short-duration and high-intensity movements that are unilateral-based and may be related to sporting and skin temperature (Tsk) asymmetries. Elevated levels of mechanical stress during eccentric contractions can induce muscle damage, inflammatory process and strength loss. Sporting asymmetries can be identified by countermovement jump (CMJ) test, but the muscle group cannot be identified by the CMJ test. So, thermography might be able to provide complementary information. The aim of this study was to investigate relationship between sporting and Tsk of lower limbs asymmetry in elite soccer players before and after a competition period. The JT evaluated the strength asymmetry. The infrared thermography (IRT) was used to evaluate Tsk asymmetry. The asymmetries were calculated by the symmetry angle. Blood tests were performed to analysis the serum concentration of creatine kinase, C-reactive protein and cortisol. The evaluations occurred before and after a competitive period. The sample was composed by two groups of 10 elite soccer players. There was significant and positive correlation between the symmetry angle of Tsk and the symmetry angle rate of force development before (r = 0,7; r² = 0,43; p = 0,03) and after (r = 0,7; r² = 0,43; p = 0,03) the competitive period. This result suggests that reduction in strength caused by muscle damage can influence in the rate of force development and Tsk asymmetries. In addition, there was significant and positive correlation between the symmetry angle of Tsk and the symmetry angle of impulse (r = 0,7; r² = 0,51; p = 0,02). After the competitive period, reduction in performance in JT, higher Tsk and high physiological demand was identified, even after 72 hours of inactivity. The result suggests that JT can be complemented by the IRT, presenting more information for the training monitoring and the sporting asymmetry and skin temperature.